REFLEKSI: MENGHIDUPKAN KEMBALI EKSISTENSI MPR DAN GARIS-GARIS BESAR HALUAN NEGARA (GBHN) (Administratio, 2019)
This paper discusses the problems between the State Policy and the State Policy Outlines (GBHN), which also explain the differences between the 1945 Constitution before and after the amendment. The development of the reality of politics and democracy in Indonesia in the reform era, with the direct election of the Presidential Election ended the Presidential Election through the MPR, while providing the President's vision and mission opportunities during the campaign as a reference in running the government, this constitutional change also has a spirit of constitutional democracy in Indonesia . After the 1945 Amendment the principle of supremacy of the constitution has replaced the supremacy of the parliament. But the polemic that was present in the community, regarding the absence of the State Policy that the country's development plans were considered inconsistent and sustainable because only based on the vision and mission of the presidential candidates during the campaign. While the desire to bring back the GBHN because it considers that with the GBHN, the country's strategic development is no longer determined by the tastes and interests of the regime itself.